Soil carbon changes after establishing woodland and agroforestry trees in a grazed pasture - Upson, Matthew A.; Burgess, Paul J.; Morison, J. I. L. (Elsevier, 2016)
This study determined the effect of two tree planting methods (woodland and a silvopastoral agroforestry system) on the soil bulk density and organic carbon content of a grassland site in lowland England. Soil organic carbon was measured in pasture, silvopastoral tree, and woodland treatments at six depths representative of 0–150 cm. Fourteen years after tree planting, the organic carbon content in the surface soil layer (0–10 cm) was greatest in the pasture (6.0 g 100 g− 1) and least in the woodland (4.6 g 100 g− 1); the value (5.3 g 100 g− 1) below the silvopastoral trees was intermediate. In the 10–20 cm layer, the organic carbon content in the woodland was 13% lower than the pasture. No treatment effects on soil carbon were detected below 20 cm. Possible reasons for the decline in surface soil carbon include a decline in grass cover and reduced soil water content. Measurements of above ground carbon storage by the trees indicated that tree planting increased overall carbon storage, with the silvopastoral system predicted to achieve a higher level of carbon storage than equivalent areas of separate woodland and pasture. A power analysis indicates that a prohibitively large number of replicates is needed to ensure a lower than 20% risk of falsely concluding no treatment differences at individual depth increments below 10 cm and cumulative depths extending below 40 cm.
Keywords: Silvopasture; Grassland; Carbon sequestration; Forest; Carbon time